STRATEGI WAKAF UANG DALAM MEGEMBANGKAN PARIWISATA HALAL (STUDI KASUS KAMPUNG AL MUNAWAR SUMATERA SELATAN SEBERANG ULU II PALEMBANG) - M. Fachry Zaiman; Maya Panorama (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
The government's great tourism potential is the government's concern in an effort to revive the Indonesian economy, such as Halal tourism. Cash Waqf as the empowerment of assets in Islam has the potential to develop Halal Tourism. Halal Tourism in Al-Munawar Village in Palembang is one example of a halal tourism object that comes from waqf activities for the surrounding community, this study aims to determine the strategy of cash waqf in developing Halal tourism in Al-Munawar Village, Palembang. The results of the study indicate that there is a need for an appropriate strategy, cash waqf is one of the strategies offered to help develop halal tourism.